Study guides

☆☆

Q: How do you solve 6x minus 3x equals 6?

Write your answer...

Submit

Still have questions?

Related questions

3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?

9x2+6x-8 = 0 (3x+4)(3x-2) = 0 Therefore: x = -4/3 or x = 2/3

Watch closely:6x = 3x + 27Subtract 3x from each side:3x = 27Divide each side by 3:x = 9

2y = 6x - 8y = 3x - 4========m(slope) = 3=========

6x - 6x = 0

6x + 6 = 3x - 2 Bring 3x to the left and subtract: 6x - 3x = 3x 3x + 6 = -2 -2 - 6 = -8 -8 / 3 X = -8/3

(3x2 - 6x)/3x = 3x(x-2)/3x = x-2, for x<>0

3x(6x - 1)

To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.

6x - 12 = 3x + 15 3x = 27 x = 9

(3x + 1) = -3 (x + 2x -1) (3x + 1) = -3 (3x - 1) 3x + 1 = -9x + 3 12x = 2 6x = 1 x = 0.16666666666666666666666666666666666666666666666666666666666666666666

x = 6 and y = -2

People also asked